Antecedents of online purchasing behaviour in the tourism sector. Issue 1 (1st February 2016) - Berbegal-Mirabent, Jasmina; Mas-Machuca, Marta; Marimon, Frederic
Abstract : Purpose: – The purpose of the paper is twofold. First, it investigates antecedents of online purchasing behaviour, taking into account the relationships between the constructs of service quality, perceived value and loyalty. Second, the study analyses up to what point men's and women's behaviours are similar. Design/methodology/approach: – A survey was sent to the general public in Spain. Respondents were required to be consumers of online travel agencies. In total, 1, 201 valid questionnaires were collected. No gender bias was detected in the sample. The data were analysed through Structural Equation Modelling to assess the proposed model. To determine non-invariant parameters across the two groups (men and women), a test for invariance was conducted. Findings: – Both functional quality and hedonic quality are shown as antecedents for perceived value, and, in turn, perceived value impacts loyalty. The impact of loyalty on purchasing behaviour is significant, though weak. Gender differences are also examined and all parameters of the model are found to operate equivalently among men and women, indicating that both groups perform similarly. Practical implications: – This paper highlights that the hedonic dimension of quality is important in adding value for customers. Accordingly, managers should reinforce this dimension and include it in their business strategy. Originality/value: – Although the link between perceived quality and value-loyalty is well-established, there are still few studies that expand this link upstream or downstream. This paper analyses the next link in this chain.